2019
DOI: 10.1186/s12954-019-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, injecting drug use, and risky sexual behavior syndemic among women who inject drugs in Kenya: a cross-sectional survey

Abstract: Background Injecting drug use (IDU) is a key driver of the HIV epidemic particularly when individuals experience psychosocial conditions and risky sexual behavior in a syndemic manner. This study sets out to assess evidence of a syndemic pattern of psychosocial conditions (IDU, depression, intimate partner violence (IPV)) on one the hand and risky sexual behavior on the other while accounting for the socio-economic disadvantage among women who inject drugs (WWID) in low-income urban settings in Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
1
12
0
2
Order By: Relevance
“…Pettes et al [31] found that after adjustment for potential social, demographic, and behavioral confounders, women with more severe depression were more likely to engage in unprotected sex and have multiple sexual partners, although in men this association was marginal. This finding was consistent with another study among women who inject drugs (WWID) in Kenya [32]. A detailed study among MSM demonstrated the relationship between depression and sexual risk may be nonlinear.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pettes et al [31] found that after adjustment for potential social, demographic, and behavioral confounders, women with more severe depression were more likely to engage in unprotected sex and have multiple sexual partners, although in men this association was marginal. This finding was consistent with another study among women who inject drugs (WWID) in Kenya [32]. A detailed study among MSM demonstrated the relationship between depression and sexual risk may be nonlinear.…”
Section: Introductionsupporting
confidence: 91%
“…Women engaged in sex work may practice more regular condom use, as shown by a studies of women with opioid use disorder [56,57] but, on the other hand, they may have elevated injection risk, such as the higher number of injections per day and receptive syringe sharing [58]. Studies from Kenya [32] and Vietnam [59 & ] confirmed that depressive symptomatology among PWID has an adverse effect on sexual and injection risk behaviors.…”
Section: Facilitators Of Sexually Transmitted Infection Risk Among Pe...mentioning
confidence: 99%
“…Among the risky behaviors, an increase in the number of sexual partners was strongly associated with susceptibility to MDD and SCZ. Promiscuity has been noted in patients with mental disorders [ 65 67 ]. However, these findings were unable to distinguish between sexual promiscuity causing mental disorders and mental disorders causing sexual promiscuity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are not enough supportive data on the prevalence estimate of undiagnosed viral infections among people with severe psychiatric disorders, it is assumed that the prevalence rates of undiagnosed HIV, HBV, and HCV believed to be considerably higher in patients with severe psychiatric disorders as compared to general population rates due to the nature of the illness which impairs their decision-making capacity [23,24], makes them to involve in risky sexual behaviors [25,26], and the reported higher magnitude of undiagnosed medical conditions (up to 80%) in people with mental illness [27,28].…”
Section: Introductionmentioning
confidence: 99%